PENGELOLAAN SUMBER DAYA MANUSIA DALAM KEPEMIMPINAN GENERASI Z DI ERA DIGITAL : (Studi Kasus Pada Organisasi Jabar Bergerak Zillenial Kota Cirebon) - Rohida, Leni; Amellia (Jurnal Ilmiah Publika, 2025)
This study aims to explore human resource management (HRM) within the context of Generation Z leadership in the digital era, using a case study of the Jabar Bergerak Zillenial organization in Cirebon City. As digital natives, Generation Z leaders possess unique characteristics in leadership and HR management. The study employs a qualitative approach with a case study method, utilizing in-depth interviews, participatory observation, and document analysis. The findings reveal that Generation Z leadership emphasizes the use of technology, rapid communication, and work flexibility. Core values such as collaboration, openness, and results orientation underpin team management practices. Digital technology adaptation also plays a key role in training, coordination, and performance evaluation. The main challenge lies in balancing young workers’ need for flexibility with the organization’s performance goals. The study recommends that Gen Z-led organizations develop adaptive HRM strategies that foster creativity, recognize individual achievements, and create a supportive work environment that enhances digital skills to improve overall effectiveness and performance.